"Are we losing our way?" Navigational aids, socio‐sensory way‐finding and the spatial awareness of young adults. Issue 3 (26th July 2018) - McCullough, David; Collins, Rebecca
Abstract : Recent advances in the accessibility and reliability of mobile technologies, roaming services and associated data have led to an increased use of modern navigational devices using Global Navigation Satellite Systems (GNSS). This paper reports on a study that explored concerns about over‐reliance on these navigational technologies, specifically among young people in the Global North. Based on an experiment in which participants were asked to navigate a series of different (unfamiliar) routes on foot, using different navigational technologies each time, we argue that routes navigated are more memorable, and the process of way‐finding is more enjoyable, when navigational tools/methods enable sensory and social interactions. GNSS aids, although claimed by participants as their preferred navigational aid, were the least enabling in this regard. We conclude that, although concerns about young people's way‐finding abilities may be overstated, the importance of sensory and social interactions with(in) environments might usefully be borne in mind in the development of future GNSS aids and locative media. Abstract : This paper reports on a study that explored the impacts of purported over‐reliance on GNSS‐based navigational aids on young adults' way‐finding ability. Participants were asked to navigate a series of different (unfamiliar) routes on foot, using different navigational technologies each time, and were subsequently asked to recreate the routes taken using sketch maps in order to explore their spatial awareness and sense of place. We conclude that, although concerns about young people's way‐finding abilities may be overstated, the importance of sensory and social interactions with(in) environments might usefully be borne in mind in the development of future GNSS aids and locative media.